La falta de control de los padres y madres de familia en el hogar y su incidencia en la disciplina de los estudiantes de educación inicial y primer año de educación general básica de la escuela Juana de Dios del cantón Machala en el periodo lectivo 2012 - 2013. - Alvarado Lindao, Rosalía Lourdes (2015)
The present document entitled: THE LACK OF PARENTS CONTROL AT HOME AND THE IMPACT ON STUDENT`S DISCIPLINE AT PRE-SCHOOL AND FIRST YEAR OF BASIC EDUCATION AT JUANA DE DIOS SCHOOL IN THE CITY OF MACHALA DURING THE ISCHOOL YEAR 2012-2013, lies on an investigative, purposeful and diagnosis process, aimed to determine the causes of the lack of control of parents at home which affects the student`s discipline. The methodology applied involves the use of the inductive, deductive, descriptive, statistical and hypothetical methods, as well as the use of observation, interview, survey and signing techniques. As a matter of conclusion of the investigation process we may infer that there are permissive parents, children who stay at other relatives care, family disintegration and limited communication between parents and children causes little control at home, this situation affects student`s discipline at Pre-school Education and First Year of General Basic Education at Juana de Dios School in the city of Machala during the school year 2012-2013.